Konformitas Individu dalam Kelompok: Studi pada Kelompok Tani Mayoritas Beranggotakan Perempuan di Kelurahan Koto Panjang Ikur Koto - Rahmadani Efendi, Dhea; Sasmita, Siska (PUBLICNESS: Journal of Public Administration Studies, 2024)
This research aims to determine the conformity of an individual farmer in a farmer group in Koto Panjang Ikur Koto Village. Conformity is refers to an influence of the social environment that can change individual attitudes and behavior so that they comply with applicable norms or rules. This research a employs a qualitative method with a descriptive approach. Researchers interviewed the parties involved, namely the extension staff of the Padang City Agricultural Service, the staff of the Agricultural Extension Center as companions to farmer groups in Koto Panjang Ikur Koto Subdistrict, Farmer Group Management, and Farmer Group members. The finding shows that  the dimensions that most dominantly influence the behavior of farmers in Koto Panjang Ikur Koto Subdistrict to carry out conformity are solidarity and trust. High levels of trust among members and close relationships between individuals (cohesion) and the group contributes to shape positive conformity. On the other hand, equality of opinion and agreement is not fully implemented, because female members tend to follow the opinion of the group leader or male members who are considered dominant, which creates negative conformity. Meanwhile, in the obedience indicator, there are still group members with low participation because they do not attend meetings held by the group.